Robôs bípedes - Design e controle utilizando trajetórias paramétricas e arquitetura amórfica - da Silva, Alysson; Machado, Alexei (Proceedings of the SBC Undergraduate Research Contest (CTIC-SBC), 2015)
In this work we propose an integrated approach for the design of humanoid robots, whose solution involves a simple control strategy that results on lower costs for large-scale production. A novel concept of organizational structure called Amorphic Architecture is presented. It allows for the deployment of hybrid controller systems and enables the generation of trajectories using a parameterization for the movement of the parts. The solution set also incorporates all the pipeline to generate the trajectories and their kinematics. Two parallel sub-systems for the graphical visualization of three-dimensional data are created. A small particle swarm optimization system is adapted to operate in real time, using a technique called Architecture O(1), in addition to the pipeline used to generate the paths. The experiments and hypothesis validation are performed through the construction of a compact humanoid robot and a research platform, at low costs.